TRAFFIC CALMING ON URBAN ROAD IN OSTRAVA-PORUBA (Perner's Contacts, 2012)
The paper deals with problems of traffic calming on four-lane divided urban road which is influence by parking maneuvers and two-lane roundabout. There are shows proposals of modifications of sections between intersections of this road and also capacity evaluation of roundabout after modification on roundabout with one-lane circulating roadway and one-lane entries and exits according to new methodology of capacity calculation which solves also capacity of exits which are influenced by pedestrian flows.